Scientific and Entrepreneurial Initiatives of Youth in the European Union - R. N. Voronina (Vestnik MGIMO-Universiteta, 2022)
Book review: Anagnostopoulou D., Skiadas D. 2022. Higher Education and Research in the European Union. Mobility Schemes, Social Rights and Youth Policies. Springer. 344 p.